Analysis of the Regional Revenue and Expenditure Budget Realization Report - M. Adam LL Dalimunthe; Natalia Titik Wiyani; Irvia Eriza (Studies in Economy and Public Policy, 2026)
Purpose: This study evaluates the effectiveness of the Bogor Regency Government's regional revenue and expenditure budget realization. It aims to assess how well local governments manage their finances in terms of revenue generation and expenditure control. Research Methodology: This study employed a quantitative descriptive approach, utilizing document analysis, surveys, and observations to gather data. The analysis focuses on comparing the planned budget with actual revenue and expenditure realizations to evaluate the fiscal performance. Results: The findings indicate that while revenue performance consistently falls short of targets, it remains effective, suggesting that the government’s revenue generation efforts, although below expectations, still meet operational requirements. In contrast, expenditure performance is highly efficient, as spending consistently stays below the allocated budget, demonstrating prudent financial management. Conclusions: This study concludes that company size and sales growth do not significantly affect tax avoidance, as measured by the Effective Tax Rate (ETR) and Cash Effective Tax Rate (CETR). The findings suggest that corporate governance, management incentives, and regulatory enforcement are more influential in determining tax avoidance behavior. Limitations: This study is limited by its reliance on secondary data, which may not fully capture the complexities of the budget process, and its focus on a single region, which limits generalizability. Contributions: The findings contribute valuable insights into local government financial management, particularly in improving fiscal discipline and resource mobilization, and offer recommendations for enhancing the effectiveness of regional budgeting practices.